ARTIKEL MORAL RESPONSIBILITY OF FOODIE INFLUENCERS IN DELIVERING FOOD REVIEWS IN PONTIANAK - Olivia, Nesha; Putri, Feby Nadia; Azzahra, Nazwa (Tujjar International Journal of Islamic Economics Development, 2024)
This study explores the moral responsibility of food influencers in delivering culinary reviews through social media, with a focus on practices in Pontianak City. In the digital era, marketing strategies have shifted significantly toward social media platforms where influencers play a crucial role in shaping product image and influencing public perception. As third-party promoters, food influencers possess considerable power in consumer decision-making. Thus, it is essential to assess the extent to which they convey information honestly, objectively, and responsibly. This research uses a descriptive qualitative approach through semi-structured interviews with two local influencers (@budakkuliner.id and @jajann.cuyy) and ten followers who had tried foods based on their recommendations. The results reveal that influencers tend to deliver neutral and polite reviews as a form of appreciation toward business owners, while still embedding honest feedback. Meanwhile, followers expect more transparent and detailed information regarding taste, portion, and pricing. These findings highlight the gap between influencer communication style and audience expectations, underscoring the need for balance between honesty, ethical communication, and social responsibility.